Different Rotavirus Strains Enter MA104 Cells through Different Endocytic Pathways: the Role of Clathrin-Mediated Endocytosis - Michelle Gutiérrez; Pavel Iša; Claudia Sánchez-San Martín; Jimena Pérez‐Vargas; Rafaela Espinosa; Carlos F. Arias; Susana López (2010)
ABSTRACT Rotaviruses, the single most important agents of acute severe gastroenteritis in children, are nonenveloped viruses formed by a three-layered capsid that encloses a genome formed by 11 segments of double-stranded RNA. The mechanism of entry of these viruses into the host cell is not well understood. The best-studied strain, RRV, which is sensitive to neuraminidase (NA) treatment of the cells, uses integrins α2β1 and αvβ3 and the heat shock protein hsc70 as receptors and enters MA104 cells through a non-clathrin-, non-caveolin-mediated pathway that depends on a functional dynamin and on the presence of cholesterol on the cell surface. In this work, using a combination of pharmacological, biochemical, and genetic approaches, we compared the entry characteristics of four rotavirus strains known to have different receptor requirements. We chose four rotavirus strains that represent all phenotypic combinations of NA resistance or sensitivity and integrin dependence or independence. We found that even though all the strains share their requirements for hsc70, dynamin, and cholesterol, three of them differ from the simian strain RRV in the endocytic pathway used. The human strain Wa, porcine strain TFR-41, and bovine strain UK seem to enter the cell through clathrin-mediated endocytosis, since treatments that inhibit this pathway block their infectivity; consistent with this entry route, these strains were sensitive to changes in the endosomal pH. The inhibition of other endocytic mechanisms, such as macropinocytosis or caveola-mediated uptake, had no effect on the internalization of the rotavirus strains tested here.